Utilization of reference books by students: a case study of Covenant University, Nigeria (2011)
This study assessed the utilization of reference books by final-year students of Covenant University, Nigeria with a view to providing valuable data to help students to get a better orientation on the use and importance of reference sources for their research work, to guide instructors and teachers on the use of library, information retrieval processes and information literacy, and to help University management, policy-makers and other stakeholders to make appropriate policies concerning the acquisitions of library materials. The survey method of research was adopted for the study. The simple random sampling technique was used in choosing the study population. The respondents for the questionnaire, interview and focus group discussion were chosen from the 400- and 500-level undergraduate students at the Covenant University. 300 copies of the questionnaires were administered to respondents. A focus group discussion was conducted with 30 participants. And 18 students were interviewed. It was revealed that students prefer online resources, which accounts for the poor usage of the hardcopy reference materials. It is, therefore, recommended that the library should intensify its information literacy skills program in order to help users maximize online reference resources. At the same time, the library should acquire more online reference sources rather than buying hard copies for a few users.